Fuzzy filtering of sensors signals in railway transport systems - Mhalla Anis; Simon Dutilleul (Journal of Fuzzy Extension and Applications)
The scope of the presented work is devoted to monitoring transport railway networks. These systems have robustness to temporal perturbations. The major paper contributes to the fuzzy filtering of sensor signals incorporating robustness parameters. This novel concept combines a conventional sensor signal filter mechanism and fuzzy logic principles. The strengths of these two techniques are leveraged to prevent control freezing and the fuzzy systems' ability to handle inaccurate information by employing fuzzy rules. Lastly, an example is shown to prove the efficiency and accuracy of the newly developed approach. The findings reveal that the fuzzy logic allows the maintenance of the travel process in a degraded mode while ensuring traffic quality and customer safety by incorporating expert knowledge.